INQUIRING VOLUNTARY TURNOVER FOR FEMALE NURSES IN PAKISTAN THROUGH FOCUSED ETHNOGRAPHY - Yasir, Muhammad; Majid, Abdul; Javed, Asad; Khan, Zubair Alam; Malik, Saqib; Naz, Farhat; Islam, Ehsan Ul (Journal of Ayub Medical College Abbottabad, 2020)
Background: Pakistan is a country with very low nurses to population rate. This problem becomes more prominent due to voluntary turnover; especially among female nurses. This problem could be attributed to several social and demographic factors. This study sought to identify the factors affecting voluntary turnover of female nurses in Pakistan. Methods: This study is qualitative in nature. Focused ethnography was used for detailed exploration of the issue of voluntary turnover among female nurses. Ethnographic interviews of informants were conducted to identify the social and organizational determinants of voluntary turnover among female nursing staff. Results: Social factors affecting voluntary turnover include religious beliefs, cultural values, lack of social respect, marital disruption, lack of psychological support. While organizational factors affecting voluntary turnover include sexual harassment, work-family conflicts, workload and job stress, emotional labour, undefined career path and lack of promotion opportunities and bullying behaviour of co-workers. Conclusion: Both social and organizational issues affect voluntary turnover among female nursing staff. Policymakers at national and organizational level must identify and address these issues to provide congenial work environment and to reduce turnover of female nurses in Pakistan. Keywords: Voluntary turnover; Social and organizational factors; Nursing; Focused ethnography